2013
DOI: 10.1073/pnas.1315273111
|View full text |Cite
|
Sign up to set email alerts
|

Democratic decisions establish stable authorities that overcome the paradox of second-order punishment

Abstract: Individuals usually punish free riders but refuse to sanction those who cooperate but do not punish. This missing second-order peer punishment is a fundamental problem for the stabilization of cooperation. To solve this problem, most societies today have implemented central authorities that punish free riders and tax evaders alike, such that second-order punishment is fully established. The emergence of such stable authorities from individual decisions, however, creates a new paradox: it seems absurd to expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 39 publications
(54 reference statements)
2
61
0
Order By: Relevance
“…Similarly, many case studies (e.g., Ostrom 1990, Cox et al 2010 and experiments (e.g., Tyran and Feld 2006, Markussen et al 2014, Hilbe et al 2014) find that enforcement is more effective when chosen by election and participatory design, than when imposed. Sinner and Salmon (2003) described a case (Convery and McDonnell 2003) in which the Irish Government sought to introduce a levy on plastic bags to improve natural scenic conditions and support ecotourism.…”
Section: Leverage Pointsmentioning
confidence: 97%
“…Similarly, many case studies (e.g., Ostrom 1990, Cox et al 2010 and experiments (e.g., Tyran and Feld 2006, Markussen et al 2014, Hilbe et al 2014) find that enforcement is more effective when chosen by election and participatory design, than when imposed. Sinner and Salmon (2003) described a case (Convery and McDonnell 2003) in which the Irish Government sought to introduce a levy on plastic bags to improve natural scenic conditions and support ecotourism.…”
Section: Leverage Pointsmentioning
confidence: 97%
“…This is referred to as social dilemma of cooperation [4,5,6,7], which has received considerable attention in recent years [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. To overcome this conflict social institutions frequently apply two control mechanisms, that is, rewards (positive incentives) for cooperation [29,30,31,32,33,34,35,36,37,38] and punishments (negative incentives) for defection [39,40,41,42,43,44,45,46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that rewards, signaling, optional participation, modest punishment, and so on, can help establish costly punishment [13,24,[29][30][31][32]. Previous findings have also indicated that binding through voting can affect endogenous choice or formation of a sanctioning institution [33,34]. Understanding how such inspiring measures can affect deformation of the existing institution remains to be explored.…”
Section: Discussionmentioning
confidence: 99%